Three Dimensional Information Extraction of Buildings Using ShadowFrom A Single Image - Mohammed, Israa (Iraqi Journal of Science, 2024)
The three dimensional information of buildings is an important issue in urbanmonitoring, planning, management and various economic activities, and as a resultof the tremendous development in the devices and remote sensing sensors, there is aneed to obtain information about geographical locations with less cost, therefore thegoal of this research is to extract the three dimensional information of buildingsusing shadow analysis appears in the 2D image and solving for the slope of view forthis shadow without the need for additional data (another overlapping image ordigital elevation model).